2007
DOI: 10.1111/j.1742-1241.2007.01316.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of insulin detemir in clinical practice: 14-week follow-up data from type 1 and type 2 diabetes patients in the PREDICTIVETM European cohort

Abstract: PREDICTIVE (Predictable Results and Experience in Diabetes through Intensification and Control to Target: An International Variability Evaluation) is a large, multi-national, open-label, prospective, observational study assessing the safety and efficacy of insulin detemir in clinical practice. A total of 20,531 patients with type 1 or 2 diabetes from 11 countries were prescribed insulin detemir and followed up after a mean of 14.4 weeks. The primary endpoint was incidence of serious adverse drug reactions (SAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
61
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 23 publications
12
61
1
1
Order By: Relevance
“…This finding is consistent with observations in another study in which a substantial reduction in daily dose of insulin glargine was noted with a transition from insulin detemir in subjects with type 2 Diabetes [9]. Several other studies have also documented a requirement of a higher daily dose of insulin detemir in comparison to insulin glargine to attain comparable glycemic control [10][11][12][13][14][15][16][17][18][19]. Thus, a higher daily dose and twice daily administration of insulin detemir may have been required to achieve desirable glycemic goal in this study as documented in previous studies in most subjects with both Type 1 and Type 2 diabetes [1,[10][11][12][13][14][15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding is consistent with observations in another study in which a substantial reduction in daily dose of insulin glargine was noted with a transition from insulin detemir in subjects with type 2 Diabetes [9]. Several other studies have also documented a requirement of a higher daily dose of insulin detemir in comparison to insulin glargine to attain comparable glycemic control [10][11][12][13][14][15][16][17][18][19]. Thus, a higher daily dose and twice daily administration of insulin detemir may have been required to achieve desirable glycemic goal in this study as documented in previous studies in most subjects with both Type 1 and Type 2 diabetes [1,[10][11][12][13][14][15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 81%
“…Several other studies have also documented a requirement of a higher daily dose of insulin detemir in comparison to insulin glargine to attain comparable glycemic control [10][11][12][13][14][15][16][17][18][19]. Thus, a higher daily dose and twice daily administration of insulin detemir may have been required to achieve desirable glycemic goal in this study as documented in previous studies in most subjects with both Type 1 and Type 2 diabetes [1,[10][11][12][13][14][15][16][17][18][19]. The requirement for a higher daily dose for insulin detemir in comparison to insulin glargine in order to achieve identical glycemic control in type 2 Diabetes is further confirmed in a recent study examining pharmacokinetics and pharmacodynamics of these insulins [20].…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial has shown noninferiority with detemir given once daily compared with twice daily in type 1 diabetes in terms of percentage of A1C (29). In an observational trial, 49% of subjects with type 1 diabetes were treated with detemir once daily (30). On the other hand, several trials designed to optimize replacement of basal insulin needs with detemir have used detemir twice daily in type 1 diabetes (26,31).…”
Section: Plasma Insulin and Substrate Concentrationsmentioning
confidence: 99%
“…Regarding long‐acting insulin analogs (e.g., insulin detemir and insulin glargine), these treatments are associated with a lower incidence of nocturnal hypoglycemia than existing intermediate type insulin preparations4, 5, 6, 7. However, there are cases where neither of these treatments, when administered using the daily basal insulin regimen, provides sufficient activity for 24 h, thus necessitating a twice‐daily regimen8, 9.…”
Section: Introductionmentioning
confidence: 99%